Surveillance for variants of SARS-CoV-2 to inform risk assessments/Surveillance des variants du SARS-CoV-2 en vue de revaluation des risques/Vigilancia de las variantes del SRAS-CoV-2 para evaluar los riesgos - Cohen, Homa Attar; Mesfin, Samuel; Ikejezie, Juniorcaius; Kassamali, Zyleen; Campbell, Finlay; Adele, Sandra; Guinko, Noe; Idoko, Friday; Mirembe, Bernadette Basuta; Mitri, Maria Elizabeth; Nezu, Ingrid; Shimizu, Kazuki; et al. (Bulletin of the World Health Organization, 2023)
Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, numerous severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have emerged, some leading to large increases in infections, hospitalizations and deaths globally. The virus's impact on public health depends on many factors, including the emergence of new viral variants and their global spread. Consequently, the early detection and surveillance of variants and characterization of their clinical effects are vital for assessing their health risk. The unprecedented capacity for viral genomic sequencing and data sharing built globally during the pandemic has enabled new variants to be rapidly detected and assessed. This article describes the main variants circulating globally between January 2020 and June 2023, the genetic features driving variant evolution, and the epidemiological impact of these variants across countries and regions. Second, we report how integrating genetic variant surveillance with epidemiological data and event-based surveillance, through a network of World Health Organization partners, supported risk assessment and helped provide guidance on pandemic responses. In addition, given the evolutionary characteristics of circulating variants and the immune status of populations, we propose future directions for the sustainable genomic surveillance of SARS-CoV-2 variants, both nationally and internationally: (i) optimizing variant surveillance by including environmental monitoring; (ii) coordinating laboratory assessment of variant evolution and phenotype; (iii) linking data on circulating variants with clinical data; and (iv) expanding genomic surveillance to additional pathogens. Experience during the COVID-19 pandemic has shown that genomic surveillance of pathogens can provide essential, timely and evidence-based information for public health decision-making.